Academic Supervision, Management, and Madrasah Principal Leadership in Strengthening Professional Competence and Performance of State Islamic Junior High Schools Teachers - Supriyanto, Aris; Suharto, Suharto; Anshori, M. Afif (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze academic supervision management and principal leadership in improving teachers' competence and performance at MTs Negeri 1 Kalianda, MTs Negeri 1 Batanghari, and MTs Negeri 2 Bandar Lampung. It also examines the role of principals in planning, implementing, and evaluating academic supervision, as well as the synergy between leadership and academic supervision in enhancing the quality of teaching and learning. This study employs a qualitative approach with a multi-site research design. Informants include school principals, vice principals, teachers, administrative staff, school committee members, and parents selected through purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking. The findings indicate that academic supervision is systematically implemented through needs analysis, clinical supervision, classroom observation, reflective mentoring, and performance-based evaluation of teachers and student learning outcomes. The impact is reflected in improved teachers' professional competence, increased work discipline, and more consistent instructional quality. In conclusion, effective academic supervision management supported by strong principal leadership significantly contributes to strengthening teachers' professional competence and performance in State Islamic Junior High Schools in Lampung Province.